Factors affecting childhood immunization: Thematic analysis of parents and healthcare workers' perceptions - Preeti Balgovind; Masoud Mohammadnezhad (Taylor & Francis Group, 2022)
Immunization against common childhood diseases is an important strategy as it is critical for reducing the global child morbidity and mortality. This review explores the perceptions of parents and HCWs toward childhood immunization. The PRISMA guideline was used to search and include the studies. Relevant electronic databases were systemically searched for the years ranging from 2000 to 2021 to identify studies reported in English. Themes were then identified using thematic analysis. A total of 44 studies met the review criteria and were summarized and categorized into 4 themes: barriers to immunization, parental knowledge, attitude and behavior (KAB), health system factors and HCWs' KAB. This review found that immunization decision-making is a complex process. Parental KAB leads to immunization decisions. HCWs were also noted to be the trusted sources of immunization information. Further research can be conducted on how to improve parents' perceptions of immunization and immunization practices.